Online Shop dan Tren Gaya Hidup Shopaholic di Kalangan Mahasiswi - Jazilah, Husainatul; Azizah, Siti (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2022)
The increasing development of online shops is one of the factors in the occurrence of shopaholic behavior. Shopping through online shops is also conducted by women, especially female students, in the village of Dadapan Lamongan. This study examines how the typology of the shopaholic lifestyle for women, especially female students, in the village of Dadapan and what factors influence women in the village of Dadapan to become shopaholic perpetrators. This study uses a qualitative method with phenomenological approach in understanding the lifestyle changes behind their actions in online shopping. The data were analyzed using the theory of consumption society Jean Baudrillard. There are several findings from this study: 1) There are several shopaholic typologies experienced by women in Dadapan village, namely, the shopaholic type who does not lose to others, the shopaholic type follows trends, the shopaholic type has impulsive symptoms on the spot, and the last is the shopaholic type that is similar. 2). Online shopping addiction can shape changes in the lifestyle of women in Dadapan Village. The factors that cause the shopaholic lifestyle are because they always follow the development of products in the online shop and always monitor the latest products in the online shop. The rise of online shop sites has also caused women in Dadapan Village, especially female students, to behave shopaholic.